THE NATIONAL UNIVERSITY OF UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article talks about the National University of Uzbekistan, which is achieving great goals in the Republic of Uzbekistan.In addition, the historical origin of the university, its current achievements, as well as the steps it has taken to reach this day will be discussed.